2021
DOI: 10.29300/ling.v7i2.5661
|View full text |Cite
|
Sign up to set email alerts
|

The Model of Listening CEFR-Based Test Specification for Higher Education

Abstract: The Common European Framework of Reference (CEFR) for Languages offers a prevalent underpinning for the development of languages syllabuses, curriculum guidelines, assessments, and textbooks. This research aimed to design appropriate CEFR-based for languages English listening test specifications for S1 English Study Program. Descriptive qualitative interpretative was used as research design of this research. The data of this research consisted of the curriculum of English language education program which focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Another implementation of CEFR in higher eduaction setting was its use in test development. [12] analised listening test specification in listening courses of several universities in Jakarta and West Java. His findings showed that the test specification was equivalent from the CEFR A1 to C1 levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another implementation of CEFR in higher eduaction setting was its use in test development. [12] analised listening test specification in listening courses of several universities in Jakarta and West Java. His findings showed that the test specification was equivalent from the CEFR A1 to C1 levels.…”
Section: Resultsmentioning
confidence: 99%
“…Each of them consisted of specifications for the mid-semester and end-semester exams. In addition to what had been done by [12], [13] also measured graduate candidates' English prociency by administering TOEIC. By doing so, they were able to know the graduate candidate CEFR level.…”
Section: Resultsmentioning
confidence: 99%